A framework for quantitative and visual analysis of white matter integrity using Diffusion Tensor Imaging. (3rd August 2009) - Liang, Xuwei; Kang, Ning; Rose, Stephen E.; Zhang, Jun
A new quantitative and visual analysis technique is developed to study the white matter integrity along fibre bundles using Diffusion Tensor Imaging (DTI) tractography. Our approach takes advantages of DTI tractography and geodesic path mapping, which establishes group-wise correspondences to allow direct cross-subject evaluation of diffusion properties. The 3D volumetric fibre bundle is approximated by streamlines reconstructed using DTI. We present the fibre bundle mask strategy to measure thin fibre bundles in group analysis. A novel isonode visualisation method is developed to facilitate the visual inspection of local white matter alterations within a neural pathway.